Efficient Data Storage And Energy Consumption Of Iot Devices Using Dsiee Method - U.Indumathi , A.R.Arunachalam , S.Ramamoorthy (International Journal of Advanced Science and Technology, 2020)
The advancement of Wireless Sensor Networks (WSNs) have improved the network protocols, smart devices with Artificial Intelligence (AI), services of wireless radio frequency and various range of other technologies and communication applications  are combined to generate Internet of Things (IoTs) as a hopeful beneficial of next generation. However, the major network for data driven has been chosen to enhance the IoT regarding data management, throughput and energy consumption. Therefore, the achievement of data reliability within WSN applications gets implemented in difficult environments is challenging due to significant constraints in sensor node (SN) infrastructure. An inexpensive WSNs infrastructure has prompted enormous distributing storage systems are proposed to focus in accomplishing data survivability instead of network reliability. The usage of decentralized storage system present in IoTs have assist for designing the data survivability scheme whereas the design of data storage system is in accordance with Decentralized Erasure Codes (DEC) which structures a simple and decentralized target code generation.  In this paper, this proposed method focus on data storage at the IoTs layer and complexity over encoding and decoding get deduced while network coding which can be done through proposed segment linear network coding (SLNC) scheme in the Data Survivability (DS)  as structure of coding for Network Coding (NC). Thus, the proposed method assists in improving the speed and efficiency in data retrieval while data get repaired due to failure and large data transmissions. Moreover, the data storage and data retrieval performance of IoT systems presented in proposed Data Survivability Integrate Energy Efficiency (DSIEE) get compared with existing DEC-EaD method.